2023
DOI: 10.3389/fpls.2023.1274943
|View full text |Cite
|
Sign up to set email alerts
|

Managing nitrogen for sustainable crop production with reduced hydrological nitrogen losses under a winter wheat–summer maize rotation system: an eight-season field study

Li Wang,
Lei Ma,
Yan Li
et al.

Abstract: Excessive nitrogen (N) application in wheat–maize cropping systems was adjusted towards more sustainable practices to reduce hydrological N losses while maintaining crop yield. In comprehensive quantification of N management effects on crop yield, N use efficiency (NUE), hydrological N losses, and soil nitrate residual across eight seasons, we have added to growing evidence of strategies beneficial for sustainable crop production with lower hydrological N losses. The results show that adjusted N practices enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Nitrogen (N), one of the most important macro elements for crop growth and development ( Makino, 2011 ; Jones et al., 2013 ), plays an important role in uplifting the grain yield and quality wheat ( Tilman et al., 2011 ; McLellan et al., 2018 ). To boost wheat productivity, high quantities of manufactured N are used in China and throughout the world ( Wang et al., 2023 ). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen (N), one of the most important macro elements for crop growth and development ( Makino, 2011 ; Jones et al., 2013 ), plays an important role in uplifting the grain yield and quality wheat ( Tilman et al., 2011 ; McLellan et al., 2018 ). To boost wheat productivity, high quantities of manufactured N are used in China and throughout the world ( Wang et al., 2023 ). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N), one of the most important macro elements for crop growth and development (Makino, 2011;Jones et al, 2013), plays an important role in uplifting the grain yield and quality wheat (Tilman et al, 2011;McLellan et al, 2018). To boost wheat productivity, high quantities of manufactured N are used in China and throughout the world (Wang et al, 2023). Liu et al (2018) concluded that a scientific N application was beneficial to root growth, alleviates the negative impact to some extent, and thus promotes water and N uptake by wheat to increase the grain yield in drought-prone areas.…”
Section: Introductionmentioning
confidence: 99%